Neuronal Injury Induces Cytokine-Induced Neutrophil Chemoattractant-1 (CINC-1) Production in Astrocytes - Takahiro Katayama; Hiroki Tanaka; Tadashi Yoshida; Takashi Uehara; Masabumi Minami (Elsevier, 2009)
Accumulating evidence indicates a pivotal role for neuroinflammation in ischemic and excitotoxic brain injury. Cytokine-induced neutrophil chemoattractant-1 (CINC-1) is a CXC chemokine implicated in the infiltration of inflammatory cells into the brain parenchyma. In this study, we investigated the effect of N-methyl-D-aspartate (NMDA)-induced neuronal injury on CINC-1 production in the organotypic cortico-striatal slice cultures. Treatment with 50 μM NMDA for 3 - 4 h caused devastating neuronal damage and increased CINC-1 production. Immunohistochemical analysis revealed that the CINC-1 immunoreactivity was predominantly detected in astrocytes. NMDA failed to induce CINC-1 production in enriched astrocyte cultures or neuron-depleted slice cultures, suggesting that NMDA acted on neuronal cells to induce astrocytic CINC-1 production. NMDA-induced CINC-1 mRNA expression was significantly inhibited by U0126, a mitogen-activated protein kinase/extracellular signal-regulated kinase (ERK) kinase (MEK) inhibitor. These results suggest that NMDA-evoked neuronal injury induced astrocytic CINC-1 production via a MEK/ERK signaling pathway. Manipulation of this signaling pathway may serve as a target for suppressing neuroinflammation and, thereby, treating ischemic brain injury. Keywords:: astrocyte, chemokine, N-methyl-D-aspartate (NMDA), mitogen-activated protein (MAP) kinase, organotypic slice culture